Higher rank BN-theory for curves of genus 4. Issue 9 (2nd September 2017) - Lange, H.; Newstead, P. E.
ABSTRACT: Higher rank Brill–Noether theory is completely known for curves of genus ≤ 3. In this paper, we investigate the theory for curves of genus 4. Some of our results apply to curves of arbitrary genus.